(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There are studies that prove that, leadership affects every thing in an organization. There are even opinions stating that leadership is a mirror to the organization it leads. In determining the success or failure of an organization, leadership is also one of the key factors. So it is undeniable that, leadership is also what determines the workload and also the job satisfaction of a staff in the organization. Discussions on leadership do not stop in a large organization, but are also widely discussed within the scope of a school. Previous studies have shown that the influence of leadership is very large in determining the climate of a school. There are also studies that lead to a more focused part of the school that is special education. This survey was conducted to examine the influence between the leadership of head teachers, workload and job satisfaction of special education teachers. The findings of this study are expected to provide a more focused picture of special education.